The Impact of Strategic Management Accounting Dimensions on Corporate Financial Performance: Emphasizing the Moderating Role of Information and Communication Technology - Zeynal Molhem, Ali Mohsen; Sojoodi, Sakineh; Haghighat, Jafarh; Ahmadian, Vahid (Business, Marketing, and Finance Open, 2025)
The purpose of this study is to investigate the effects of strategic management accounting (SMA) dimensions on corporate financial performance and to examine the moderating role of information and communication technology (ICT) in this relationship. The statistical population consists of companies operating in Iraq. Using a sampling method, 311 valid questionnaires were collected and analyzed through the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach in SmartPLS software. The results reveal that strategic decision-making and costing exert the strongest positive and significant effects on financial performance. ICT also demonstrates a positive and significant direct effect on financial performance, while firm size exhibits a weak but statistically significant positive effect. The remaining SMA dimensions do not show significant effects. Among the five moderating effects examined, only the moderating role of ICT in the relationship between costing and financial performance was found to be significant (at the 10% level).The findings indicate that improving the financial performance of Iraqi companies is primarily achieved through strengthening strategic decision-making, adopting advanced costing practices, and directly leveraging ICT. Accordingly, it is recommended that Iraqi managers place greater emphasis on enhancing strategic decision-making processes and precise costing practices, while treating investment in ICT infrastructure as a vital complement to these processes.